SOURCE PARAMETERS OF MODERATE AND STRONG EARTHQUAKES IN THE BROADER AREA OF ZAKYNTHOS ISLAND (W. GREECE) FROM REGIONAL AND TELESEISMIC DIGITAL RECORDINGS - Chousianitis, K.; Agalos, A.; Papadimitriou, P.; Lagios, E.; Makropoulos, K. (Bulletin of the Geological Society of Greece, 2010)
The source parameters of all the moderate and strong events that occurred in the broader area of Zakynthos Island for the period 1997–2009 are determined using two different techniques depending on epicentral distance. For the strong events we employed teleseismic body-wave modeling between 30° and 90°, while for moderate events a regional moment tensor inversion approach was used. In both cases we used broadband waveform data with a good signal-to-noise ratio. The calculated focal mechanisms are representative of the displacement and strain fields of the broader area. Those associated with the Cephalonia transform fault are consistent with dextral strike-slip motion. The area between the island of Zakynthos and the Western coast of Peloponnese is also characterized by strike–slip faulting, while reverse faulting is mainly observed south of Zakynthos Island. Using both techniques, we also retrieved the source parameters of the biggest events of the seismic sequence of April 2006 near the southern coast of Zakynthos Island. The depths of the located events of the sequence vary mainly between 10 and 25 km. The fault plane solutions revealed thrust type faulting in all cases, something which can be related with upward motions in the southern part of the Island observed by DGPS measurements.